Reflecting critically on the researcher-participant encounter in focus groups: Racialized interactions, contestations and (re)presentations of South Africa's "protest culture". Issue 1 (2nd January 2022) - Cornell, Josephine; Malherbe, Nick; Suffla, Shahnaaz; Seedat, Mohamed
ABSTRACT: South Africa has a considerable history of public protest from which a contemporary "culture of protest" has emerged. Despite the wide-ranging body of research on protest in South Africa, few studies have considered critically the discursive space in which researchers and participants are embedded. In this article, we use discursive psychology to examine reflexively how South African protesters discursively contest, (re)produce, and negotiate South Africa's culture of protest in the presence of their comrades and researchers. Our analysis focuses on the making of "protest culture, " discursive resistance in the research setting, and the effect of researcher silence. We conclude by calling for protest researchers to remain sensitive to power differentials operating in research settings, while establishing a discursive space within these settings wherein participants feel heard and researchers do not attempt to mute their presence to achieve "neutrality".